Tinerii – grup expus riscului de excluziune socială: analizarea factorilor care le îngreunează situaţia pe piaţa muncii şi în educaţie - Ionescu, Ionela (Calitatea Vieții, 2017)
This article focuses on presenting/ analyzing the factors that hampers the social inclusion of youth people, as well as the support, measures and interventions offered to this vulnerable group. Social inclusion of young people refers to a process that seeks to provide the necessary support in achieving the potential of every person, regardless of their experience or the circumstances in which they carry out their life. To support the active participation of young people in socio-economic, cultural and political life, it must be ensured both the opportunities for access to education, employment and to decent living conditions. We focused on two areas of action from the youth social inclusion, education and employment, but also to present the state of post-institutionalized youth. Both at EU level and Romania, the problem of youth unemployment (especially in this category are included those who are engaged in some form of education) is so severe, that has triggered various financing programs for young people. The main risk factor for young people is the lack of a job, on long-term this factor threatens the social inclusion of youth. Among the most important factors of vulnerability to social exclusion of young people on the labor market there were identified the following: the low qualification, inadequacy of the qualification according to the labor market, the passivity of labor market, a precarious financial situation, the low level or lack of social support, an insufficient or no institutional support. In order to prevent, effectively, and to reduce the risk of exclusion for young people, must rectify determinants that generate social inequalities.